Krig og fred i Mali: Baggrund og perspektiver - Signe Marie Cold-Ravnkilde (Danish Institute for International Studies (DIIS), 2013)
– On April 25, 2013, UN's Security Council established a 12,600-strong peacekeeping force for Mali. The United Nations Multidimensional Integrated Stabilization Mission (MINUSMA) is to take over and continue the security and stabilization task that the French-led military operation in cooperation with UN's African-led International Support Mission to Mali, AFISMA, initiated in January 2013. The aim of this report is to present a number of long- and short-term perspectives for the recently initiated peace- and state-building process in Mali by focusing on the historical, structural and political causes of the crisis in Mali. Understanding these causes and handling their derived conflict potentials provide a minimum of prerequisites for establishing long-term peace. The report is structured according to four intertwined conflict potentials: Mali's fragile state, the status and background of the Tuareg rebellion, the organized crime and the regional cooperation. ...
Keywords: 300